Outer Membrane Lipoprotein Lip40 Modulates Adherence, Colonization, and Virulence of Actinobacillus pleuropneumoniae - Liu, Jinlin; Cao, Yurou; Gao, Lulu; Zhang, Li; Gong, Siying; Yang, Jihong; Zhao, Haobin; Yang, Dengfu; Zhao, Jin; Meng, Jianzhong; Gao, Qishuang; Qi, Chao (Frontiers in Microbiology, 2018)
Bacterial lipoproteins are a set of membrane proteins with various functions; many of which are virulence factors of pathogenic bacteria. In the present study, we investigated the role of an outer membrane lipoprotein Lip40 in the pathogenesis of Actinobacillus pleuropneumoniae. A mutant strain (Δlip40) lacking Lip40 and a complemented strain (CΔlip40) were constructed. Δlip40 exhibited reduced adherence to SJPL cells. The ability of the Δlip40 mutant to colonize the mouse lung tissues was significantly impaired compared to that of the wild type and complementation strains. Furthermore, an infection assay revealed that pigs infected with Δlip40 showed fewer clinical signs and lung lesions, indicating that Lip40 contributed to the development of porcine pleuropneumonia. Collectively, our data suggest that Lip40 is involved in the virulence of A. pleuropneumoniae.